MAGNETIC SUSCEPTIBILITY CHANGES CORRELATED WITH PALEOENVIRONMENTAL AND LITHOLOGICAL CHANGES, WITHIN BOREHOLE CORES ON EITHER SIDES OF THE KALAMAKI-ISTHMIA FAULT IN CORINTH CANAL - Pallikarakis, A.; Papanikolaou, I.; Triantaphyllou, M.; Grützner, C.; Migiros, G.; Reicherter, K.; Mason, J.; Schneiderwind, S. (Bulletin of the Geological Society of Greece, 2016)
Τhe most important active fault that intersects the eastern tip of Corinth Canal,the Kalamaki-Isthmia fault, is studied in detail, involving data analysis from nine boreholes, magnetic susceptibility measurements within boreholes and paleoenvironmental interpretations. Samples taken from boreholes were analysed and paleoenvironmental changes in the sequence are described. We correlate magnetic susceptibility (MS) measurements with paleoenvironmental and lithological alternations within the boreholes. We have ascribed low MS values to marine highstand deposits and high MS values to lowstand terrestrial deposits. Glacioeustatic sea level changes and tectonic movements have led to a very complicated lithosedimentary pattern that involves subaerial exposure, fluvialterrestrial, lagoonal, shallow marine environments and possibly even some lake sediments. Our results indicate that the Kalamaki fault is active and has a low slip rate of 0.05±0.02 mm/yr.